2006
DOI: 10.1007/s00439-006-0264-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a regulatory SNP in the retinol binding protein 4 gene associated with type 2 diabetes in Mongolia

Abstract: Increased levels of retinol binding protein 4 (RBP4) in serum is associated with insulin resistance. To examine this further, the genomic region of RBP4 was genetically surveyed in Mongolian people, who as a group are suffering from a recent rapid increase in diabetes. The RBP4 gene was screened by DHPLC system, and the PCR fragments which showed heteroduplex peaks in multiple samples were followed by direct sequencing to identify common polymorphisms in 48 Mongolian diabetic samples. Identified single nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 21 publications
3
97
4
Order By: Relevance
“…In conclusion, consistent with previously reported findings in mice and in human studies (1,6,7), several RBP4 SNPs and their haplotypes are likely to affect measures of insulin resistance (fasting plasma insulin and 2-h plasma glucose) and related traits (BMI, WHR, and circulating FFAs), as well as RBP4 mRNA levels in visceral adipose tissue in humans. These effects may ultimately result in type 2 diabetes, which is in line with the observed association of the A-G-G-T-G-C haplotype with increased risk of type 2 diabetes in the present study.…”
Section: Rbp4 and Susceptibility To Type 2 Diabetessupporting
confidence: 91%
See 2 more Smart Citations
“…In conclusion, consistent with previously reported findings in mice and in human studies (1,6,7), several RBP4 SNPs and their haplotypes are likely to affect measures of insulin resistance (fasting plasma insulin and 2-h plasma glucose) and related traits (BMI, WHR, and circulating FFAs), as well as RBP4 mRNA levels in visceral adipose tissue in humans. These effects may ultimately result in type 2 diabetes, which is in line with the observed association of the A-G-G-T-G-C haplotype with increased risk of type 2 diabetes in the present study.…”
Section: Rbp4 and Susceptibility To Type 2 Diabetessupporting
confidence: 91%
“…The highly conserved region surrounding rs3758539 matches human transcriptional binding sites for MAZ (11) and R1/R2/Sp1 for the major allele G (12,13) and c-Ets-2 for the minor allele A (14). Furthermore, this SNP seems to influence the transcription efficiency in a hepatocarcinoma cell line as well as the binding efficiency of hepatocyte nuclear factor 1␣ to the motif (6). Regarding the association of the RBP4 haplotype with mRNA levels, this also indicates a potential functional relevance of the noncoding RBP4 variants in the putative promoter region.…”
Section: Rbp4 and Susceptibility To Type 2 Diabetesmentioning
confidence: 89%
See 1 more Smart Citation
“…Two haplotypes (SNP (risk allele): rs3758538(A), rs3758539(G), rs10882283(G), c248C44TOC(T), rs12265684(G), rs10882273(C); and rs3758539(G), 390COG(G), 406TOC(T), rs36014035(G), rs12265684(G), rs34571439(T), rs12766992(G), rs10882273(C)) are significantly increased in Caucasians with T2D when compared with healthy controls (33,48). Four SNPs in Mongolian population (SNP (risk allele): rs3758539(A), rs7094671(T), rs12265684(C), and 7542TOdel(del)) and a haplotype in South Indian population (rs3758538(C), rs3758539(T), rs36014035(G), and rs34571439(T)) have also been determined that are associated with T2D (31,49). Haplotype (SNP (risk allele)) rs3758538(A), rs3758539(G), rs10882283(G), c248C44TOC(T), rs12265684(G), rs10882273(C)) is also associated with higher mean fasting plasma insulin and 2 h plasma glucose in OGTT in non-diabetic Caucasians (33).…”
Section: Rbp4 In Insulin Resistance and T2d: Clinical Studiesmentioning
confidence: 99%
“…Haplotype (SNP (risk allele)) rs3758538(A), rs3758539(G), rs10882283(G), c248C44TOC(T), rs12265684(G), rs10882273(C)) is also associated with higher mean fasting plasma insulin and 2 h plasma glucose in OGTT in non-diabetic Caucasians (33). In Mongolians, SNP in the regulatory region of the RBP4 gene (SNP (risk allele) rs3758539(A)) is associated with increased circulating RBP4 levels in T2D subjects (49). Recently, three SNPs (SNP (risk allele): rs974456 (T), rs736118 (A), and rs4886578 (A)) and two haplotypes (SNP (risk allele): rs974456(C), rs736118(G), rs4886578(G) and (rs974456(T), rs736118(A), rs4886578(A)) in the gene encoding a high-affinity cell surface receptor for RBP4, STRA6, have been identified that are associated with T2D (31).…”
Section: Rbp4 In Insulin Resistance and T2d: Clinical Studiesmentioning
confidence: 99%